Zeurinal a low-maintenance public urinal that uses zeolite for odor elimination - Axalan, Christine Joy C.
Restrooms, especially men's, whether those found in malls, schools, or public areas are often associated with pungent odor. The public urinals supplied by the MMDA provide privacy and a place for men to urinate but the lack of maintenance which results to pungent odor discourages other possible users from using it. Urine is made of 95% water and 5% Urea, and Urea, when mixed with fresh water, hydrolyses as ammonia which is a colorless pungent gas and causes the urinal to smell. With this in mind, a study was connected to explore different material options that would aid in minimizing odor and thus providing a design that incorporates the use of Zeolite which is an ammonia-adsorbing mineral, with consideration to the lack of maintenance and choice of material. Zeurinal: a low-maintenance public urinal that uses Zeolite for odor elimination introduces the use of Zeolite and with its design, allows maximum adsorption of ammonia. The zeolites will be replaced and recharged quarterly. With lesser maintenance effort and with Zeolite's adsorption capability, urinals will no longer be a scare for users and passersby.